CRYPTOCURRENCY REGULATIONS: AN INTERNATIONAL PERSPECTIVE AND IMPLICATIONS FOR VIETNAM - Lam, Nguyen Tung; Hien, Nguyen Van (International Journal of Research -GRANTHAALAYAH, 2025)
The paper analyses how mature regulatory regimes in the European Union, Japan, the United States govern cryptocurrencies and distils lessons that can shape a coherent, innovation-friendly yet risk-aware framework for Vietnam, where regulation is still fragmented and largely prohibitive. Adopting a socio-legal methodology, the dissertation combines doctrinal review of statutes and policy papers with comparative, case-study, and policy-oriented analysis. Legal instruments, enforcement actions and market outcomes in benchmark jurisdictions are systematically compared to Vietnam’s current rules. Qualitative content drawn from legislation, court cases, and expert commentaries is triangulated to identify regulatory gaps and best-practice components. Vietnam recognises crypto-assets as property and enforces rigorous AML rules, yet its regime is fragmented: payment bans, scant consumer protection and no regulatory sandbox stifle innovation and competitiveness. Comparative review shows that jurisdictions with precise definitions, tiered licensing, and proportionate safeguards, such as the EU’s MiCA and Japan’s PSA/FIEA, enjoy stronger market integrity and capital inflows. This study outlines a four-stage roadmap for Vietnam: codify crypto definitions and licensing; broaden AML/CFT and disclosure duties; embed consumer-protection and tax rules; and launch sandboxes to nurture compliant innovation, closing gaps and enhancing financial stability. This paper is the first to synthesize doctrinal, comparative, and policy-oriented analyses of EU MiCA, Japan’s PSA/FIEA, the United States’ dual federal–state regime, and to convert the insights into a phased roadmap expressly tailored to Vietnam’s civil-law system and policy priorities. By moving beyond earlier descriptive surveys to expose legal inconsistencies, measure consumer-protection gaps, and propose a unified regulator plus sandbox pilot, it delivers actionable guidance for Vietnamese decision-makers and fills the regional research void on balanced, innovation-friendly crypto governance in emerging economies.